The Difference of Impact Strength in Acrylic Resin Self-Cured with the Addition of Zirconium Dioxide (ZrO2) Nanoparticles - Annete Juwita; Widaningsih; Puguh Bayu Prabowo (Denta Journal Kedokteran Gigi, 2018)
Background: Self-cured acrylic resin is a material used for repairing broken and fractured dentures. Zirconium dioxide (ZrO2) is a reinforcing material that is being developed as an additive to the acrylic resin. Purpose: to determine the effect of zirconium dioxide (ZrO2) addition on self-cured acrylic resin on impact strength. Material and Methods: This study was a true experimental laboratory study with the design of a post-test only control group design, using 24 pieces of self-cured acrylic resin measuring 65 x 10 x 2.5 mm divided into 4 groups with and without zirconium addition dioxide (ZrO2) nanoparticles. Zirconium dioxide (ZrO2) nanoparticles were silanized first by mixing the silane coupling agent. Furthermore, the impact strength was tested on the plate. The data obtained were analyzed using the One Way ANOVA test. Results: there were significant differences in the impact strength between the groups with a significance value of 0,000 (p <0.05). Conclusion: there was a difference in the increase of impact strength in acrylic resin self-cured with the addition of ZrO2 nanoparticles concentrations of 3%, 5%, and 7%.